Draft Genome Sequence of a Moderately Halophilic Bacillus megaterium Strain, MSP20.1, Isolated from a Saltern of the Little Rann of Kutch, India - Pal, Kamal Krishna (American Society for Microbiology, 2014)
The 4.37-Mbp draft genome of a moderately halophilic Bacillus megaterium strain, MSP20.1, isolated from a saltern of the Little Rann of Kutch, India, is reported here. To understand the mechanism(s) of moderate halophilism and to isolate the gene(s) involved in osmotolerance and adaptation, the genome of MSP20.1 was sequenced.